An Accelerated Introduction to Memetic Algorithms. - Moscato, Pablo; Cotta-Porras, Carlos (Springer, 2018)
Memetic algorithms (MAs) are optimization techniques based on the orchestrated interplay between global and local search components and have the exploitation of specific problem knowledge as one of their guiding principles. In its most classical form, a MA is typically composed of an underlying population-based engine onto which a local search component is integrated. These aspects are described in this chapter in some detail, paying particular attention to design and integration issues. After this description of the basic architecture of MAs, we move to different algorithmic extensions that give rise to more sophisticated memetic approaches. After providing a meta-review of the numerous practical applications of MAs, we close this chapter with an overview of current perspectives of memetic algorithms.
Política de acceso abierto tomada de: https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Computación evolutiva; Algoritmos evolutivos; Memetic algorithms; Evolutionary computation; Memetic computing